A prediction risk score for HIV among adolescent girls and young women in South Africa : identifying those in need of HIV pre-exposure prophylaxis - Moyo, Reuben Christopher (Stellenbosch : Stellenbosch University, 2022)
Thesis (MSc)--Stellenbosch University, 2022.